Metodologiya poznaniya sporta i optimizatsiya upravleniya im - Piloyan, R. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
By the purpose of this research was the attempt to bring methodological arrangement to the study of sport and to optimize the management by this complex public phenomenon. Its achievement will facilitate the disclosing of the basic rules, which it is necessary to adhere by the one who is engaged in the study of sports. It is accepted to name these rules as the methodological principles, which line now can be precisely formulated: The principle of the concrete definition of the subject of research; The principle of the primacy of competition; The principle of system; The principle of activity. It is necessary to adhere them to the researchers with the purposes of penetration into essence of such a complex phenomenon as sport.